A cognitive linguistic approach to teaching English idioms to EFL students: experimental results - Hung, Bui Phu (Penerbit Universiti Kebangsaan Malaysia, 2019)
This study aims to apply basic concepts in cognitive linguistics to teaching English idioms to EFL students. English idioms expose their inherent difficulties to EFL learners because people of different languages usually have different conceptualizations. Words in idioms do not carry their literal but conceptualized semantics. Cognitive linguistics, grounded in cognitive, social, and communicative theories, hypothesize idioms as examples of conceptual metaphors. Twelve idioms about finance were taught to 50 Vietnamese first-year EFL college students divided into two experimental groups for CL-based treatment and treatment for rote-learning, and one control group with no treatment. The experimental groups received 4-step treatments: warm-up, instruction, drill practice, and productive task. The results showed that the group receiving CL-based treatment outperformed the group applying rote-learning in both immediate posttest and delayed posttests for receptive and productive knowledge of the instructed idioms. The control group did not make any significant gain from the prettest to the posttests. The results suggest that students’ awareness of conceptual metaphors help them remember the target items long. Further studies can include measures of both explicit and implicit knowledge of the idioms as a result of CL-based treatment in other contexts.